ROS-mediated NLRP3 inflammasome activation participates in the response against Neospora caninum infection - Lu Li; Xiao-Cen Wang; Peng-Tao Gong; Nan Zhang; Xu Zhang; Shan Li; Xin Li; Shao-Xiong Liu; Xiao-Xu Zhang; Wei Li; Jian-Hua Li; Xi-Chen Zhang (Parasites & Vectors, 2020)
Abstract Background Neospora caninum is an obligate intracellular protozoan that causes neosporosis, N. caninum infection is a major cause of abortion in cattle worldwide. Currently, specific treatment for neosporosis is not available. The NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome is a cytoplasmic protein complex that plays an important role in host defense against N. caninum infection, but the underlying mechanisms are poorly understood. Methods The reactive oxygen species (ROS) inhibitor and the ROS inducer, wild-type (WT) and NLRP3-deficient peritoneal macrophages or mice were used to investigate the role of ROS in NLRP3 inflammasome activation and controlling parasite burdens. ROS production, cell death and cell viability, production of inflammasome-mediated IL-1β or IL-18, cleavage of caspase-1 and NLRP3 expression, as well as parasite burdens were detected. Results In vitro, N. caninum induced ROS generation in a dose-dependent manner in peritoneal macrophages. The pretreatment of ROS inhibitor N-acetyl-l-cysteine (NAC) significantly attenuated N. caninum-induced ROS production, LDH release, IL-1β secretion and NLRP3 expression, whereas N. caninum proliferation was notably increased. In contrary, the ROS inducer pyrogallol (PG) significantly enhanced ROS production and NLRP3 inflammasome activity and decreased the parasite burden in N. caninum-infected peritoneal macrophages. NADPH-dependent ROS-mediated NLRP3 inflammasome activation induced by N. caninum can also be confirmed by using the NADPH oxidase inhibitor diphenyleneiodonium chloride (DPI). However, the NAC or DPI pre-treatment or PG treatment did not significantly alter N. caninum-induced inflammasome activities and parasite proliferation in Nlrp3 −/− peritoneal macrophages. In vivo, IL-18 releases in serum and parasite burdens in peritoneal exudate cells were significantly increased in PG-treated WT mice after infection with N. caninum; however, IL-18 productions and parasite burdens were not changed in PG-treated Nlrp3 −/− mice. Furthermore, PG treatment in WT mice infected with N. caninum significantly decreased the mortality, weight loss and parasite burdens in tissues and histopathological lesions. Conclusions Neospora caninum-induced NADPH-dependent ROS generation plays an important role in NLRP3 inflammasome activation and controlling parasites. The ROS inducer PG can control N. caninum infection mainly by promoting NLRP3 inflammasome activation. ROS-mediated NLRP3 inflammasome axis can be a potential therapeutic target for neosporosis.